Development of metering device for precise hybrid rice seeder - Omar, Mohamad Fakhrul Zaman; Daud, Abu Hasan; Fithri, Khairul (Engineering & Technology Research, 2017)
Hybrid rice has proven capable to deliver higher yield than ordinary variety. It has yield potential of more than 10t/ha. In direct seeding, hybrid rice requires about 25kg/ha of seed compared to 120kg/ha of ordinary variety. A precise metering mechanism is required to meet the optimum use of hybrid rice. A seeder is developed by MARDI to cater the usage for this variety. It consists of mainframe, seeder unit and wheel drive. It is to be mounted on prime mover and applying mechanical drive to function. The metering device regulates the amount of seed production precisely for 2-3 seed per drop. An experiment has been conducted to determine the most suitable metering setting that could optimize the use of seed per area. From the result, it shown that several metering setting of the device will affect the amount of seed directly. The developed seeder is made specifically for hybrid rice and from the experiment result, the device manage to fulfill the requirement needed in term of lowering the cost of seed and device maintenance as well as user friendly.